Incidence of major adverse cardiac events following non-cardiac surgery. Issue 5 (14th October 2020) - Sazgary, Lorraine; Puelacher, Christian; Lurati Buse, Giovanna; Glarner, Noemi; Lampart, Andreas; Bolliger, Daniel; Steiner, Luzius; Gürke, Lorenz; Wolff, Thomas; Mujagic, Edin; Schaeren, Stefan; Lardinois, Didier; et al.
Abstract: Aims: Major adverse cardiac events (MACE) triggered by non-cardiac surgery are prognostically important perioperative complications. However, due to often asymptomatic presentation, the incidence and timing of postoperative MACE are incompletely understood. Methods and results: We conducted a prospective observational study implementing a perioperative screening for postoperative MACE [cardiovascular death (CVD), acute heart failure (AHF), haemodynamically relevant arrhythmias, spontaneous myocardial infarction (MI), and perioperative myocardial infarction/injury (PMI)] in patients at increased cardiovascular risk (≥65 years OR ≥45 years with history of cardiovascular disease) undergoing non-cardiac surgery at a tertiary hospital. All patients received serial measurements of cardiac troponin to detect asymptomatic MACE. Among 2265 patients (mean age 73 years, 43.4% women), the incidence of MACE was 15.2% within 30 days, and 20.6% within 365 days. CVD occurred in 1.2% [95% confidence interval (CI) 0.9–1.8] and in 3.7% (95% CI 3.0–4.5), haemodynamically relevant arrhythmias in 1.2% (95% CI 0.9–1.8) and in 2.1% (95% CI 1.6–2.8), AHF in 1.6% (95% CI 1.2–2.2) and in 4.2% (95% CI 3.4–5.1), spontaneous MI in 0.5% (95% CI 0.3–0.9) and in 1.6% (95% CI 1.2–2.2), and PMI in 13.2% (95% CI 11.9–14.7) and in 14.8% (95% CI 13.4–16.4) within 30 days and within 365 days, respectively. The MACE-incidence was increased above presumed baseline rate until Day 135 (95% CI 104–163), indicating a vulnerable period of 3–5 months. Conclusion: One out of five high-risk patients undergoing non-cardiac surgery will develop one or more MACE within 365 days. The risk for MACE remains increased for about 5 months after non-cardiac surgery. Trial registration: https://www.clinicaltrials.gov . Unique identifier: NCT02573532.